Global Hunger Index: Interactive map application - International Food Policy Research Institute (Welthungerhilfe, 2015)
The Global Hunger Index (GHI) interactive map application is an online tool designed for exploration of the GHI data. Access to the application is at http://ghi.ifpri.org/ and it is housed in a GitHub repository where IFPRI will maintain and upload new versions when they are available. https://github.com/IFPRI/Global-Hunger-Index